Emotional state using DASS-21 in post-COVID-19 patients in primary health care - Carrillo-Avilés, Ángel Francisco; García-Torres, Osvaldo; Obeso-Sandoval, Indira Susana (Horizonte Sanitario, 2023)
Objective: “Determine the emotional state following the DASS-21 in post-COVID-19 patients at the first level of health care”. Material and methods: Observational, cross-sectional, descriptive study conducting a survey on the emotional state (DASS-21; Lovibond and Lovibond, 1995) in post-COVID-19 patients in a sample of 70 patients from the Family Medicine Unit No. 34 annex Ambulatory Care Medical Unit of La Peace, Baja California Sur. A statistical analysis was carried out with frequencies, percentages for nominal qualitative variables, with measures of central tendency and dispersion in quantitative variables, with determination of chi2. With prior authorization from the local research committee and ethics committee. Results: 45 female patients were found (64.3%), age 39.41 ± 13.930, with a statistical significance between anxiety and presence of severe symptoms with p= 0.014 (95%CI 0.000-0.042), depression and age group p= 0.029 (95%CI % 0.000-0.068); and no significance was found with stress. Conclusion: Anxiety mildly and extremely severely affects post-COVID-19 patients related to the presence of severe symptoms, the depression detected was moderate and is related to the age group, while the stress detected was mild and did not present an association of variables. Keywords: Coronavirus infections; Anxiety; Psychological distress; Depression; Emotional Adjustment.